A Silvopastoral System in the North Atlantic Zone of Costa Rica: Combining Indigenous Timber Species with Dairy Pasture Swards - Moulaert- Quiros, A; Mueller, J P; Villarreal, M; Piedra, R; Villalobos, L (UKnowledge, 2024)
The objective of this study was to design, establish and monitor a silvo pastoral experiment on a dairy farm in the northern Atlantic region of Costa Rica. Indigenous timber species, Vochysia guatemalensis and Hyeronima alchorneoides were used together with or without the tropical pasture legume, Arachis pintoi in a split plot design with a 4 x 2 x 2 factorial arrangement. First year establishment was good for the tree component (2.3 to 10 % mortality) but poor for A. pintoi (4 to 5 % of sward). Poor legume establishment was attributed to lax grazing management and excess competition from existing Brachiaria sp. A. Pintoi was reestablished in July 1996 after an adjustment of stocking rate. This experimental project is planned for a 10 year period which corresponds to the expected rotation length for harvesting the indigenous timber species.